Key characteristics in designing HIV interventions at a glance - Mona Larki; Elham Manouchehri (HIV & AIDS Review. International Journal of HIV-Related Problems)
Acquired immune deficiency syndrome (AIDS) is one of the most serious problems confronting human society, with significant healthcare costs, societal concerns, and focus on the youth. Worldwide commitments to reduce AIDS-related mortality and new human immunodeficiency virus (HIV) infections to under 500,000 by the end of 2020 failed last year, as 680,000 people have died from AIDS-related diseases and 1.5 million have become infected with HIV. Therefore, HIV prevention remains one of the world's highest priorities in terms of public health and development. Characteristics of HIV interventions are divided into seven categories: comprehensive health literacy programs, gender-responsive, holistic content, management of intervention by competent specialists, involvement of people living with HIV, utilization of multiple and innovative techniques, and allocating a specific time frame. Identifying essential characteristics of HIV preventive programs may have a beneficial impact on intervention design. In addition, creating effective interventions can minimize the number of new HIV cases of infection and associated diseases, impacting the community and health system. Researchers and policy-makers interested in developing HIV/AIDS-related interventions may find the results of this study useful.